The Oldest Vocation : Christian Motherhood in the Medieval West - Atkinson, Clarissa W. (Book collections on Project MUSE., 1991)
"After tracing the roots of medieval ideologies of motherhood in early Christianity, the author reconstructs the physiological assumptions underlying medieval notions about women's bodies and reproduction. She then describes the development of "spiritual motherhood" both as a concept emerging out of monastic ideologies in the early Middle Ages and as a reality in the lives of certain remarkable women" - Book jacket.